Effects of drought at different periods of wheat development on the leaf photosynthetic apparatus and productivity - Morgun, V. V.; Stasik, O. O.; Kiriziy, D. A.; Sokolovska-Sergiienko, O. G.; Makharynska , N. M. (Regulatory Mechanisms in Biosystems, 2019)
The problem of drought impact on crop productivity is especially relevant for the leading cereal – wheat, since significant cultivation areas of this crop are located in risky farming zones. The aim of our studies was to compare the peculiarities of drought impact during the period of vegetative growth and reproductive development on the chlorophyll content, activity of chloroplast antioxidant enzymes, the rate of carbon dioxide gas exchange and transpiration as well as productivity of the wheat plants. The studies were carried out on bread winter wheat plants (Triticum aestivum L.) of the Astarta and Natalka varieties grown in a pot experiment. The plants were watered daily to maintain the soil moisture level in the pots in the range 70–60% of field capacity. Drought treatment involving decrease in soil moisture to 30% of the field capacity was applied to some of the plants at late stem elongation stage (BBCH 37-45) and to other plants at heading-anthesis (BBCH 59-65) while control plants were watered as usual. After 7 days of drought, the watering of treated plants was resumed to maintain the soil moisture at the level of control plants until the harvest. The penultimate leaf at the late stem elongation stage and flag leaf at the heading–anthesis period were used for measurements of photosynthetic apparatus response to drought. Plants of both varieties treated at stem elongation stage showed lower decline in the photosynthetic activity, chlorophyll content and grain productivity than those treated at heading-anthesis. The results obtained indicated that photosynthetic apparatus of wheat has a higher drought tolerance at the stem elongation stage than during the heading-anthesis stage. Furthermore, plants stressed at the stem elongation stage revealed better compensatory growth of lateral productive shoots due to superior supply of plants with assimilates after drought termination. Astarta variety had a more drought-tolerant photosynthetic apparatus and higher grain productivity in both well-watered and drought conditions as compared to Natalka variety. The differences between varieties were more contrasting when drought was applied at heading-anthesis.